Physico-Chemical Studies of Bore Wells Water of Various Places in and around Limkheda (Gujarat) - Rana, A.K.; Kharodawala, M.J.; Patel, J.M.; Rai, R.K.; Patel, B.S.; Dabhi, H.R. (Asian Journal of Chemistry, 2010)
Physico-chemical studies such as temperature, pH, dissolved oxygen, total dissolved solids, chloride, total alkalinity, calcium and magnesium hardness, sulphate, phosphate and nitrate of bore wells water was carried out from eighteen sampling stations of Limkheda town and its some interior adivasi (backward) area during the year 2001, in order to assess water quality index.